Analysis of Eco-Friendly and Superior-Growing Paper to Address Environmental Issues in Kindergartens (KARTU) - Dayati Erni Cahyaningrum; Arini Inayatul Fajriyah; Sulianto, Joko (Universitas PGRI Semarang, 2024)
The purpose of the Kartu Research initiative is to address environmental issues related to the large amounts of paper used in various games and activities in several kindergartens, which are often simply discarded, burned, sold by weight, or taken home by the children without introducing other meaningful solutions for educational purposes. This research focuses on promoting recycling concepts by utilizing used materials to teach children about environmentally friendly behaviors and raising awareness of the importance of protecting the surrounding environment. This study employed a qualitative approach with students as subjects and was conducted during the first semester at a kindergarten in Slawi. Data analysis primarily followed the Miles and Huberman method, involving activities such as data collection, data display, and conclusion drawing. Additionally, documentation, observation, and interviews were conducted with relevant sources to integrate and collect data for analysis. The research results show that using eco-friendly paper at the studied kindergarten became an unforgettable experience and a gradual process in building children’s awareness of the importance of protecting the environment. Through the process of making plant cards from recycled paper, children were directly involved in recycling and learned about the negative impacts of burning, selling, or discarding paper, which pollutes the environment. They also understood that it is better to bury the paper to enable it to decompose, allowing it to eventually grow into vegetable plants since it had already been recycled into beneficial plant cards. The KARTU program implemented at this kindergarten was designed to instill eco-friendly values in children through various activities, including recycling, planting, marketing, selling, and maintenance as educational initiatives. This program has proven successful, though it is not yet optimal and still needs refinement, as it was an enjoyable first recycling experience for both teachers and students.